(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Estimating understandability of object oriented software early in the development process; particularly at design phase greatly reduce the overall development cost and effort. To design and deliver quality products inside time and financial plan understandability plays a very important role. This paper shows the need and significance of understandability at design phase and build up a multivariate linear model “Understandability Estimation Model” for Object-Oriented Design. Developed model estimates the understandability of class diagrams in respect of their internal design properties. In this research paper an attempt has been made to propose an understandability estimation framework as a first contribution. A relation between object oriented design properties and understandability has been established as a second contribution. In third contribution, despite the fact that, in order to estimate class diagram’s understandability the researcher further developed multivariate models. In conclusion the proposed Understandability models have been authenticated via experimental test.